Anti-money laundering in the Greater Bay Area: effectiveness, strategies and compliance - Hoi, Kuan Io (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Three Essays on Foreign Trade, Offshoring and International Rivalry - Lei, Weng Chi (University of Washington, 2018)
This dissertation consists of three essays, covering the topics of foreign trade, offshoring and international rivalry. In particular, Chapter 1 analyzes the strategic capacity allocation of an international oligopoly. Because a line of products shares specific inputs that are fixed in the short run, a multiproduct oligopolist faces a capacity constraint in the production. Not being able to produce the desirable quantities to meet demand, an oligopolist strategically allocates its capacity among different products against its rival. If the market were monopolistic, a firm would mainly concern the effective profitability of a product when allocating its capacity and when responding to a capacity expansion. Identical duopolists that compete in a Cournot fashion should have identical capacity allocation. However, in a sequential game, while the Stackelberg leader allocates all its scarce capacity towards the more profitable product, the follower should still allocate some capacity towards the unprofitable product. This matches the observation that Boeing, the incumbent in the large commercial aircrafts (LCA) industry, specializes in smaller planes, while Airbus allocates resources more evenly towards both superjumbo planes and smaller planes. Chapter 2 provides an explanation to the observation that international oligopolists, which are similar in many ways (subject to the same state of technology, have equal market shares, etc.), may engage in significantly different degrees of offshoring. Different from previous studies, which considered fragmentation to be affected by global exogenous factors only, this essay sees fragmentation as an endogenous variable. A firm can invest on R&D of its own fragmentation technology to enable certain degrees of fragmentation, so that offshoring of those fragmented subparts can be achieved. An important implication of endogenous fragmentation is that the government now has a policy alternative to export subsidy. Very often, when export subsidy is prohibited under an FTA, a government has incentive to subsidize fragmentation of a firm, which can stimulate both export and offshoring. Chapter 3 investigates Macao's and Singapore's questionable goal to diversify among two tourism services—gambling and convention. Macao has a cost advantage in gambling while Singapore has a cost advantage in convention. When a city operates as a regional monopoly, the simple multiproduct model shows that it is optimal for a city to diversify in response to an expansion in the markets of the tourism services. If the two cities operate as a Cournot duopoly instead, there will be a higher degree of product differentiation between the cities. Yet, both cities diversify more when there is a market expansion. On the other hand, Osaka is a potential entrant. The three-city model shows that if Osaka's relative cost of producing convention is even lower than Singapore’s, both Macao and Singapore will produce greater proportions of gambling compared to the two-city case. In general, Macao and Singapore respond to Osaka’s rivalry by strategizing their product mixes to avoid head-on competition with Osaka.
Keywords: 0501:Economics; Economics; Foreign trade; International rivalry; Offshoring; Social sciences; Strategic capacity allocation